Neurospora : contributions of a model organism - Davis, Rowland H. (Oxford University Press, 2000)
1. A Brief History. Discovery. Original genetic studies. The question of gene action. Later developments in Neurospora research. Nomenclature. 2. The Biology of Neurospora. Lifestyle and habitat. Asexual cycle. Sexual cycle. Cells and organelles. Nutrition, physiology and growth. Behavior. 3. Genome and Mitosis. The nuclear genome of N. crassa. Nuclei and nuclear division. The RIP process. Transposable elements. Centromeres. Telomeres. 17S, 5.8S, and 25S Ribosomal DNA (nucleolus organizer). 5S rDNA. Unique-sequence genes. 4. Meiosis, Genetic Analysis, and Recombination Models. Cytology of post.